ANALISIS STRATEGI GURU DALAM PEMBENTUKAN KARAKTER RELIGIUS SISWA KELAS IV DI SDN 2 KLESEM - Ayu Papudani, Sentika; Trisnawaty, Wulan; Martini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to describe 1) teacher strategies in forming the religious character of fourth-grade students at SDN 2 Klesem, 2) the religious character of fourth-grade students from the results of the implementation of teacher strategies. This study uses qualitative research with a descriptive approach. The subjects were Islamic Religious Education teachers, grade IV homeroom teachers, and 21 grade IV students. The data collection techniques are observation, interviews, and documentation. The data validity checking techniques are source triangulation and technical triangulation. Data analysis techniques are in the form of data reduction, data presentation and drawing conclusions. Based on the data analysis, it is concluded that: 1) teacher strategies in forming the religious character of fourth-grade students at SDN 2 Klesem are the habituation approach (through praying, tadarus, dhuha prayer, memorization, and Asmaul Husna), role models, integration in learning, providing motivation and rewards, implementing 3S culture (Smile, Greet, Say Hello), participation in religious and extracurricular activities, 2) the religious character of fourth-grade students from the results of the implementation of teacher strategies is starting to form and is shown by the consistency of increasing student habituation participation in every aspect and indicator that exists for three weeks. Teacher strategies have proven effective in instilling religious values in students.